2015
DOI: 10.1108/ijchm-04-2014-0173
|View full text |Cite
|
Sign up to set email alerts
|

The role of servicescape and image perceptions of customers on behavioral intentions in the hotel industry

Abstract: Purpose – The purpose of this study is to examine the relationships between servicescape components, image and behavioral intentions within the framework of hotel businesses. Design/methodology/approach – Relationships between specified variables were tested with structural equation modeling (SEM) using a sample of 410 hotel customers. Findings – It was found that servicescape com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
141
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(176 citation statements)
references
References 86 publications
14
141
0
11
Order By: Relevance
“…Our study results showed that overall image positively affects the three outcome variables; intentions to use (0.912, p < 0.05), word-of-mouth intentions (0.926, p < 0.05) and willingness to pay more (0.504, p < 0.05). As a first attempt to identify the effect of overall image on intentions to use, word-of-mouth intentions and willingness to pay more in an environmentally friendly airline context, the results are consistent with previous studies [57,85,86]. That is, when passengers have a positive overall image about an environmentally friendly airline, they are more likely to (1) take an environmentally friendly airline when traveling; (2) recommend an environmentally friendly airline to others; and (3) spend extra in order to take an environmentally friendly airline.…”
Section: Theoretical Implicationssupporting
confidence: 80%
See 1 more Smart Citation
“…Our study results showed that overall image positively affects the three outcome variables; intentions to use (0.912, p < 0.05), word-of-mouth intentions (0.926, p < 0.05) and willingness to pay more (0.504, p < 0.05). As a first attempt to identify the effect of overall image on intentions to use, word-of-mouth intentions and willingness to pay more in an environmentally friendly airline context, the results are consistent with previous studies [57,85,86]. That is, when passengers have a positive overall image about an environmentally friendly airline, they are more likely to (1) take an environmentally friendly airline when traveling; (2) recommend an environmentally friendly airline to others; and (3) spend extra in order to take an environmentally friendly airline.…”
Section: Theoretical Implicationssupporting
confidence: 80%
“…For example, Han and Hyun [57] collected data from 286 passengers in order to find the role of overall image in the cruise industry and suggested that overall image has a positive impact on intentions to use. In addition, Durna, Dedeoglu and Balikçioglu [86] investigated how overall image influences word-of-mouth in the hotel industry. They analyzed data from 410 hotel customers and found that overall image is an important predictor of word-of-mouth.…”
Section: The Effect Of Overall Image On Its Outcome Variablesmentioning
confidence: 99%
“…Penelitian-penelitian sebelumnya menyebutkan bahwa hotel image dapat dipengaruhi oleh servicescape yang terdiri dari social servicescape dan physical servicescape (Durna et al, 2015;Aal & Abbas, 2016).…”
Section: Tabel 1 Hotel Bintang 5 DI Dki Jakarta Berdasarkan Tahun Penunclassified
“…Penelitian ini mengacu pada penelitian sebelumnya yang dilakukan oleh Durna et al, (2015) serta Aal & Abbas (2016). Variabel yang digunakan serta pengukuran dalam penelitian ini diambil dan diadaptasi dari literatur penelitian terkait.…”
Section: Metode Penelitianunclassified
See 1 more Smart Citation